2019
DOI: 10.1016/j.jviromet.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a SYBR green-based real-time RT-PCR assay for rapid detection of the emerging swine acute diarrhea syndrome coronavirus

Abstract: A B S T R A C TSwine acute diarrhea syndrome coronavirus (SADS-CoV) is a novel coronavirus which was associated with severe diarrhea disease in pigs. SADS-CoV was first detected and identified as the causative agent of a devastating swine disease outbreak in southern China in 2017. Routine monitoring and early detection of the source of infection is therefore integral to the prevention and control of SADS-CoV infection. In this study, a SYBR greenbased real-time reverse transcription quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…PDCoV was first reported in early February of 2014 in the United States, in March of 2014 in Canada, in April of 2014 in Korea [4][5][6]. It seemed that like PEDV and TGEV [21,22], disease caused by PDCoV infection mainly peaks in colder months between January and April. However, in the present study, one swine farm outbroke PDCoV in June, which is a very hot month in Henan Province of China, indicating that we need to continue monitoring the prevalence of PDCoV in all the seasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDCoV was first reported in early February of 2014 in the United States, in March of 2014 in Canada, in April of 2014 in Korea [4][5][6]. It seemed that like PEDV and TGEV [21,22], disease caused by PDCoV infection mainly peaks in colder months between January and April. However, in the present study, one swine farm outbroke PDCoV in June, which is a very hot month in Henan Province of China, indicating that we need to continue monitoring the prevalence of PDCoV in all the seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Primers of PDCoV, PEDV, TGEV and PoRVA/B/C were designed and preserved by the Key Laboratory for Animal-derived Food Safety of Henan Province. Primers of SADS-CoV were synthetized that targeted the mostly conserved gene of SADS-CoV [22]. The primers were shown in Table 1.…”
Section: Rt-pcr Detectionmentioning
confidence: 99%
“…Lei Ma et al (2020) compared the data obtained from RT-qPCR based on (SYBR Green (SG) together with a probe which was designed for M gene sequence in the viral genome, and the findings revealed that the detection limit for such methods was ten copies per microliter of the sample. The efficiency of the SG method and probe-based RT-PCR was 73.81% and 53.57%, respectively [ 49 ]. Moreover, the sensitivity of the RT-PCR technique for nasopharyngeal secretions, throat discharge, urinary tract secretions, and a fecal sample was reported to be 60–68%, 65–72%, 50–54%, and 57–63%, respectively.…”
Section: Covid-19 Diagnosismentioning
confidence: 99%
“…The fight against infectious diseases caused by viruses is still challenging and regarded as an endless task for public health care [ 1 ]. Coronaviruses are the members of Coronaviridae family and can cause respiratory and neurological diseases [ 2 , 3 ]. Six human coronaviruses (HCoVs) have been detected, including, HCoV-229E, HCoV-HKU1, HCoV-OC43, HCoV NL63 to date, severe acute respiratory syndrome coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV).…”
Section: Introductionmentioning
confidence: 99%